Development Of Statistics Teaching Modules For Improving Critical Thinking Abilities Of Grade XI - Putri Bertua Aurelia Pasaribu; Rick Hunter Simanungkali; Firman Pangaribuan (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This research was motivated by the low critical thinking skills among eleventh-grade students at SMA Negeri 2 Pematangsiantar. Preliminary analysis showed that 61.1% of students were unable to recognize problems and identify the known and questioned information. The research method used was Research and Development (R&D), adapting the 4D model (Define, Design, Develop, Disseminate). The developed module meets the validation criteria from material and media experts. The module was declared highly practical, as indicated by the 90.4% positive response rate from students. The module was proven effective in improving students' critical thinking skills. The increase in students' critical thinking skills was in the high category, with an N-Gain score of 0.71. Furthermore, the classical learning mastery of students reached 94.4%, exceeding the minimum mastery criterion (80%).